Cross-language orthographic neighborhood density effects in Dutch–English and Spanish–English bilinguals - Biedermann, Britta; Beyersmann, Elisabeth; Blosfelds, Mara; Macapagal, Christella; Rosevear, Ashleigh; Marinovic, Welber (Frontiers in Language Sciences, 2024)
Processing a word in a second language (L2) may be hindered or helped by simultaneous activation of similar words present in L2 and in addition by similar words that occur in the first language (L1). Precise mechanisms for influencing variables within L2 and cross-language processing are still little understood. The current visual word recognition study explored orthographic neighbourhood density effects in L2 English, replicating the effects for Dutch-English, while expanding the exploration to a new language combination, Spanish-English. The within and across language effects were explored in a group of Dutch-English and Spanish-English bilinguals. English L2 targets were subdivided into four neighbourhood density (ND) conditions: high-L1+high-L2, high-L1+low-L2, low-L1+high-L2, and low-L1+low-L2. For Experiment 1, an analysis of generalized linear mixed-effects models (GLMM) revealed that Dutch (L1)-English (L2) bilinguals showed a facilitatory main effect of English ND on reaction times and error rates. However, an inhibitory main effect of L1 Dutch ND on L2 visual word recognition was only observed for reaction times but not for error rates. Overall, no interaction was detected between L1 and L2 ND for reaction times or error rates. Additionally, a factorial permutation test confirmed the L2 facilitatory effect on both reaction times and error rates, while it supported an L1 inhibitory effect for error rates only. In Experiment 2, a GLMM analysis replicated the L2 facilitatory effect on reaction times in Spanish (L1)-English (L2) bilinguals but did not reveal an inhibitory main effect of L1 on L2 word recognition. Instead, we found a significant interaction between English (L2) and Spanish (L1) ND. Reaction time patterns were confirmed by the non-parametric analysis, though with only a marginally significant interaction. For error rates, no effect of ND was detected using GLMM. However, the permutation test revealed significant L2 facilitatory and L1 inhibitory effects on L2 word recognition, but no significant interaction. Our data confirm a robust L2 facilitatory main effect of ND on reaction times across experiments and analyses, while L1 inhibitory main and interaction effects were less robust across experiments and analyses. The latter may be dependent on language specificity, and speaker characteristics.